2020
DOI: 10.1073/pnas.2004392117
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic extended synaptotagmin-3 contributes to the development of dietary obesity and related metabolic disorders

Abstract: The C2 domain containing protein extended synaptotagmin (E-Syt) plays important roles in both lipid homeostasis and the intracellular signaling; however, its role in physiology remains largely unknown. Here, we show that hypothalamic E-Syt3 plays a critical role in diet-induced obesity (DIO). E-Syt3 is characteristically expressed in the hypothalamic nuclei. Whole-body or proopiomelanocortin (POMC) neuron-specific ablation of E-Syt3 ameliorated DIO and related comorbidities, including glucose intolerance and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Studies of those proteins in specific tissues will be a way to identify their physiological roles. Recent studies have already confirmed this possibility (Guo et al, 2017 ; Kirmiz et al, 2018a ; Zhang et al, 2020 ). On the other hand, some regulators' functions are not related to ER-PM contact sites (Tremblay et al, 2016 ; El Kasmi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies of those proteins in specific tissues will be a way to identify their physiological roles. Recent studies have already confirmed this possibility (Guo et al, 2017 ; Kirmiz et al, 2018a ; Zhang et al, 2020 ). On the other hand, some regulators' functions are not related to ER-PM contact sites (Tremblay et al, 2016 ; El Kasmi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 83%
“…However, E-Syts and tricalbins do have physiological effects. For example, E-Syts can maintain PM lipid homeostasis, promote nerve transmission and synaptic growth, modulate virus-induced membrane fusion, mediate the endocytosis of FGFR, and play roles in insulin secretion and diet-induced obesity development (Saheki et al, 2016 ; Tremblay et al, 2016 ; Kikuma et al, 2017 ; El Kasmi et al, 2018 ; Xie et al, 2019 ; Nath et al, 2020 ; Zhang et al, 2020 ). Tricalbins act in maintaining PM integrity (Toulmay and Prinz, 2012 ; Collado et al, 2019 ).…”
Section: Lipid Exchanges At Er-pm Contact Sitesmentioning
confidence: 99%
“…Mice were anesthetized by intraperitoneal injection of 4% chloral hydrate (0.13 ml/10 g) for all surgeries. After virus injection, up to five mice were kept in one cage on chow diet (9.4% kcal from fat) ( 11 ), and cages were changed twice a week. The daily food intake of mice is calculated by cage: the total food intake of the cage/the number of mice.…”
Section: Methodsmentioning
confidence: 99%
“…Several neuronal subsets, including agouti-related peptide (AgRP)-producing neurons, are implicated in this process (Gautron et al, 2015;Morton et al, 2014). Previous work has identified various molecules and pathways, including PTP1b (Bence et al, 2006), IKKb (Zhang et al, 2008), ER stress (Ozcan et al, 2009;Zhang et al, 2008), JNK1 (Belgardt et al, 2010), GABA (g-aminobutyric acid) (Vong et al, 2011), synaptotagmin-4 (Zhang et al, 2011), PPAR-g (Lu et al, 2011;Ryan et al, 2011), NOS1 (Leshan et al, 2012), mitofusin (Dietrich et al, 2013;Schneeberger et al, 2013), P2Y6 (Steculorum et al, 2015), glucocorticoid (Quarta et al, 2017), Na v 1.7 (Branco et al, 2016), adenosine 1 receptor (Wu et al, 2017), and extended synaptotagmin-3 (Zhang et al, 2020), that play a significant role in maintaining energy balance or obesity development. It remains unclear, however, whether hypothalamic neuronal SOCE is crucial in either or both of these processes.…”
Section: Article Llmentioning
confidence: 99%
“…The procedures have been described previously (Zhang et al, 2008(Zhang et al, , 2020. To inject viruses into Arc nucleus, mice were anesthetized with Avertin (300 mg kg -1 ), and then were placed on an ultra-precise stereotaxic instrument (David Kopf, Tujunga, CA).…”
Section: Stereotaxic Surgerymentioning
confidence: 99%